Word definition skills in elementary school children – The contribution of bilingualism, cognitive factors, and social factors. - Rosqvist, Ida; Andersson, Ketty; Sandgren, Olof; Lyberg-Åhlander, Viveka; Hansson, Kristina; SahlÉn, Birgitta (International Journal of Speech-Language Pathology, 2022)
Purpose: Vocabulary relates to overall language proficiency and is important for academic success. Word definition (WD) tasks can be used to assess vocabulary depth and definition skills. We investigate monolingual and bilingual children's performances on a WD task, and how bilingualism, level of parental education, school characteristics (proportion of students with Swedish as second language and proportion of parents with tertiary education), CELF-4 Core Language Score, and non-verbal IQ contribute to their performance. We also evaluate the level of difficulty of the test items and the test's internal consistency. Method: Two hundred and eight children (mean age 7:8, range 6:8–9:0) were assessed with a 10-item WD task. Amount of information included in the definitions gave the WD score and number of words with at least partially correct information gave a Word knowledge score. Result: The bilingual group had lower scores on both measures. In isolation bilingualism explained 15% of the variance of the WD score. With all background factors included, the only significant predictor was CELF-4 Core Language Score, uniquely explaining 24.3% of the variance. Response patterns on the WD score were similar between groups. Internal consistency was > α = 0.7 for both measurements. Conclusion: Bilingual children performed lower than monolingual children on a WD task, but bilingualism alone cannot explain poor results.